Student’s individual educational trajectory: stages and requirements for building - Belchenko, Vladimir Evgenievich; Harutyunyan, Anna Alexandrovna; Nikolaeva, Lyudmila Georgievna; Bogdanova, Ardema Vladimirovna; Lapshin, Nikolay Alexandrovich; Aleksanyan, Georgy Ashotovich (Nuances: Estudos sobre Educação, 2021)
The article discusses the individual educational trajectory, the stages of building individual educational trajectory, the requirements for building individual educational trajectory, and the individualization of the educational process. An individual educational trajectory can be defined as a personal way of realizing the student’s personal potential in the educational process. The building and implementation of individual educational trajectories are possible as long as students implement a logically justified chain of choices in the course of their educational activities that lead to the necessary result. A special role in the building and implementation of individual educational trajectories (routes) is played by the nature of the interaction between the teacher and the student. The most successful is considered to be psychological and pedagogical support, i.e., a system of individual support in personal and professional development, as well as counseling in the formation of individual professional experience and mastering professional skills.